Organizing Online Events - Steiner, Petra; Röthlingshöfer, Natalie; Dörrbecker, Nicola; Debusmann, Robert; Jassat, Stephanie; von der Osten, Alice; Geißler, Lilly; Exzellenzcluster Afrika Multiple, Universität Bayreuth; Exzellenzcluster Afrika Multipel, Universität Bayreuth (2022)
This is a compilation of over 100 slides which were presented in different block courses on Organizing Online Events that were attended by colleagues and members of The Africa Multiple Cluster of Excellence at the University of Bayreuth. Each of them was tailored for different events and attendees – from new student assistants to professors of partner institutions. We used Zoom Meetings and Zoom Webinars, but also administrative platforms and OBS and Restream for streaming onto other platforms. Most courses were structured into eight modules, comprising Basics, Installation of Zoom Webinars/Meetings, Recording, Streaming, Mixed Formats, (internal) Administrative Tasks, Problem Management, and After the Event. Some modules are designed for beginners, some for experienced colleagues.
Keywords: Internet Videoconferencing; Webinar; Zoom